Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1088/0004-637x/740/2/63
|View full text |Cite
|
Sign up to set email alerts
|

GAS AND DUST IN A SUBMILLIMETER GALAXY ATz= 4.24 FROM THEHERSCHELATLAS

Abstract: We report ground-based follow-up observations of the exceptional source,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
176
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 168 publications
(190 citation statements)
references
References 72 publications
14
176
0
Order By: Relevance
“…Maiolino et al, 2005;Iono et al, 2006;Maiolino et al, 2009;Walter et al, 2009;Wagg et al, 2010;Stacey et al, 2010;Gallerani et al, 2012;Carniani et al, 2013), SMGs (e.g. Ivison et al, 2010d;Stacey et al, 2010;Cox et al, 2011;De Breuck et al, 2011;Swinbank et al, 2012;Wagg et al, 2012;George et al, 2013;Huynh et al, 2013) and normal star-forming galaxies (e.g. Graciá-Carpio et al, 2011) at high-redshift have all been detected in [CII].…”
Section: Atomic Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Maiolino et al, 2005;Iono et al, 2006;Maiolino et al, 2009;Walter et al, 2009;Wagg et al, 2010;Stacey et al, 2010;Gallerani et al, 2012;Carniani et al, 2013), SMGs (e.g. Ivison et al, 2010d;Stacey et al, 2010;Cox et al, 2011;De Breuck et al, 2011;Swinbank et al, 2012;Wagg et al, 2012;George et al, 2013;Huynh et al, 2013) and normal star-forming galaxies (e.g. Graciá-Carpio et al, 2011) at high-redshift have all been detected in [CII].…”
Section: Atomic Linesmentioning
confidence: 99%
“…The data at moderate redshifts is from Farrah et al (2013) and Rigopoulou et al (2014). The high-z data is subdivided into quasars and SMGs, and comes from Cox et al (2011) Willott et al (2013) A number of studies have used extremely high resolution [CII] observations to constrain the size of the emitting region of high-z quasar host galaxies. Walter et al (2009) derived a source size of ∼ 1.5 kpc, and suggested that the galaxy was undergoing an Eddington-limited starburst event.…”
Section: [Cii] Morphologies and Dynamicsmentioning
confidence: 99%
“…Seventeen have been added to the number of z > 4 [CII] detections in the past decade (Maiolino et al 2005(Maiolino et al , 2009Iono et al 2006;Wagg et al 2010;Ivison et al 2010;De Breuck et al 2011;Cox et al 2011;Swinbank et al 2012;Venemans et al 2012;Walter et al 2012;Riechers et al 2013;Wang et al 2013;Rawle et al 2014;De Breuck et al 2014;Neri et al 2014). Many of these objects have been selected based on the presence of a luminous active galactic nuclei (AGN; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Maiolino et al 2005;Stacey et al 2010;Wang et al 2013), while others have been selected as starburst galaxies (e.g. Ivison et al 2010;Hailey-Dunsheath et al 2010;Stacey et al 2010;Cox et al 2011;Swinbank et al 2012;Walter et al 2012;Riechers et al 2013;Brisbin et al 2015). This leads to a heterogeneous sample of high-z [CII] detections, containing a mixture of AGN and starburst-dominated systems.…”
Section: Introductionmentioning
confidence: 99%
“…Source-count models seem to need a redshift cutoff at ∼ 4 to explain 850 and 1100 µm counts (see section 12). The Herschel-Hermes survey detects plenty of z > 3 galaxies (eg Rowan-Robinson et al 2010) and Herschel-ATLAS has detected a z = 4.2 starburst galaxy (Cox et al 2011). But it still seems surprising that we have not detected more z > 4 submillimetre galaxies.…”
Section: Submillimetre Galaxiesmentioning
confidence: 75%